Supramolecular cyclodextrin complexes of biologically active nitrogen heterocycles (Chemical Bulletin of Kazakh National University, 2024)
The review is devoted to the rapidly developing field of modern supramolecular chemistry - cyclodextrin complexes of biologically active nitrogen heterocycles, such as piperidines, piperazines, morpholines and pyridines. Interest in cyclodextrin complexes is growing due to the search and construction of supramolecular assemblies for targeted drug delivery. The latter is achieved as a result of supramolecular self-assembly, based on the principles of molecular recognition, and is one of the areas of modern chemistry, leading to the creation of new materials with new properties.This review fully demonstrates the ongoing scientific and practical interest in the problem of encapsulation with cyclodextrins, including nanoencapsulation. Encapsulation with cyclodextrins provides a wide range of advantages: obtaining solid dosage forms from liquid ones, stabilizing and protecting active substances from the adverse effects of external factors, increasing solubility, increasing bioavailability, reducing toxicity, prolonging action, etc.The presented review includes recent advances in the field of supramolecular complexes of biologically active nitrogen heterocycles with cyclodextrins and concludes with a discussion and identification of future promising directions for research. The review presents the results of supramolecular self-assembly of biologically active azaheterocycles with cyclodextrins.
Keywords: supramolecular complexes; cyclodextrins; biological activity; nitrogen heterocycles.; piperidines; piperazines; morpholines; pyridines